2000
DOI: 10.1346/ccmn.2000.0480506
|View full text |Cite
|
Sign up to set email alerts
|

Geology and Characterization of Two Hydrothermal Nontronites from Weathered Metamorphic Rocks at the Uley Graphite Mine, South Australia

Abstract: Abstrac~Mining operations during the early 1990s at Uley Graphite Mine near Port Lincoln on southern Eyre Peninsula, South Australia, uncovered abundant nontronite veins in deeply weathered granulite facies schist, gneiss, and amphibolite of Palaeoproterozoic age. Two types of nontronite are present: a bright yellowish-green clay (NAu-1) distributed as veinlets and diffuse alteration zones within kaolinized schist and gneiss, and a massive to earthy, dark-brown clay (NAu-2) infilling fracture networks mainly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
141
2
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(163 citation statements)
references
References 20 publications
18
141
2
2
Order By: Relevance
“…However, as has been demonstrated here for synthetic nontronites, the NIR combination region clearly indicates the presence of only one band corresponding to δFe 3+ 2 -OH vibrations. Thus, assignment of this 841-850 cm −1 band in synthetic nontronite to a δFe 3+ 2 -OH bending mode as previously hypothesized by some authors for natural nontronites (Goodman et al, 1976;Keeling et al, 2000;Gates, 2005) is therefore inadvisable.…”
Section: Lattice Bandssupporting
confidence: 62%
“…However, as has been demonstrated here for synthetic nontronites, the NIR combination region clearly indicates the presence of only one band corresponding to δFe 3+ 2 -OH vibrations. Thus, assignment of this 841-850 cm −1 band in synthetic nontronite to a δFe 3+ 2 -OH bending mode as previously hypothesized by some authors for natural nontronites (Goodman et al, 1976;Keeling et al, 2000;Gates, 2005) is therefore inadvisable.…”
Section: Lattice Bandssupporting
confidence: 62%
“…Compositions by ICP are from Actlabs; compositions by XRF were obtained at University of Massachusetts with the exception of the Totavi basalt, which is a LANL reference material. Reagent compositions (CaSO 4 as anhydrite and lithium tetraborate) are as-certified carbonate and iron oxyhydroxide (Keeling et al 2000) while KGa-2 has been reported to have 3 % anatase, 1 % crandallite, and traces of mica and/or illite (Chipera and Bish 2001). Our XRD analysis of the as-received NAu-2 sample shows presence of a trace amount of feldspar; anatase is present in the as-received KGa-2 ( Fig.…”
Section: Ceramic Synthesis Tests and Fabricationmentioning
confidence: 64%
“…The clay mineral used in this study is a nontronite from Southern Australia (25). Nontronite is a naturally occurring swelling dioctahedral clay mineral related to the montmorillonitebeidellite series in which most aluminum atoms are replaced by iron (III) ions.…”
Section: Resultsmentioning
confidence: 99%